El liderazgo transformacional en una institución educativa pública - Martínez Contreras, Ysrael Alberto (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
The transformational leadership allows managers influence their teachers who recognize and attributed control to the director. The research investigated what are the characteristics of the transformational leadership of the director of a public educational institution of the UGEL 07. Through the study we recognized the features of transformational leadership in the director. The research identified three elements of the transformational leadership attributed to the director. The views expressed by the teachers and the data obtained from the respondents in order to obtain a description of the exercise of transformational leadership in the selected institution were also examined.

El liderazgo transformacional permite a los directivos influenciar en sus docentes quienes reconocen y atribuyen mando al director. La investigación indagó cuáles son las características del liderazgo transformacional del director de una institución educativa pública de la UGEL 07. A través del estudio reconocimos las características del liderazgo transformacional en el director. En la investigación se identificaron tres elementos del liderazgo transformacional atribuidos al director. También se analizaron las opiniones vertidas por los docentes y los datos obtenidos de los encuestados a fin de obtener una descripción del ejercicio del liderazgo transformacional en la institución seleccionada.
The Transformational Leadership in a Public Educational Institution
Keywords: Leadership; Role Of The Director; Perception; Teachers; Liderazgo; Papel del Director; Percepción; Profesores; https://purl.org/pe-repo/ocde/ford#5.03.00